The Effect of Return on Investment, Basic Earning Power and Investment Opportunity Set on Dividend Payout Ratio (Study of Infrastructure Firm Listed at Indonesia Stock Exchange In 2017- 2021) - Rahma Lia Fauziah; Nor Norisanti; Deni Muhammad Daniel (Journal of International Conference Proceedings (JICP), 2022)
The aim of this research is to find out how influential the of Return on Investment (ROI), Basic Earning Power (BEP) and Investment Opportunity Set (IOS) on the Dividend Payout Ratio (DPR) of infrastructure companies listed in Indonesia Stock Exchange in the periode 2017-2021. The sample used in this study was 7 companies that had been selected using the purposive sampling technique. The method used in this study is descriptive and associative research methods with a quantitative. The data analysis technique used multiple linear regression through the SPSS version 16 application. Simultaneously, from the researches showed that Return on Investment, Basic Earning Power and Investment Opportunity Set with proxy Market to Book Value of Equity Ratio did not significantly affect on the Dividend Payout Ratio. Based on the coefficient of determination test is 0.372, it can be interpreted that the effect of Return on Investment (ROI), Basic Earning Power (BEP) and Investment Opportunity Set (IOS) on the Dividend Payout Ratio (DPR) is 13.83%. The remaining 86.17% was influenced by other factors that were not addressed in this study. Keywords: Return on Investment, Basic Earning Power, Investment Opportunity Set, Dividend Payout Ratio.